Development of a Social Reconstruction Curriculum Based on Religious Moderation in Madrasah Aliah Negeri Throughout East Java - Utomo, Tri Prasetiyo (Proceedings of Annual Conference for Muslim Scholars, 2023)
Madrasah Aliah Negeri (MAN) 1 Tulungagung is an Islamic educational institution that prioritizes balance with current developments and the social environment of the community. MAN 1 Tulungagung vision and mission, namely the realization of a generation of Muslims who are intelligent, superior in science and technology, have good morals, and have an environmental culture. Research at MAN 1 Tulungagung aims to determine the formulation of the development of religious moderation values and the effectiveness of developing religious moderation values. This research uses a qualitative approach, with the type of field research. The results showed that the values of religious moderation were developed by a team of religious moderation values developers, moderation experts, and madrasa heads. The development of religious moderation values results in tolerance, moderation, balance, uprightness, freedom of worship, and moral orientation of al-karimah. While the effectiveness of developing religious moderation values can be measured from; level of knowledge of moderation, understanding, awareness, moderate activity, and implementation of moderation.